2015
DOI: 10.1007/s11669-015-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Zn-V-Sb System at 450 °C

Abstract: Phase diagram of the Zn-V-Sb ternary system has been studied experimentally by means of scanning electron microscopy coupled with energy-dispersive spectrometric and x-ray diffraction. Twelve different tri-phase regions could be confirmed in this system at 450°C. Moreover, a new ternary compound named VZnSb, whose composition range spanned from 30.4-32.4 at.% V, 30.5-34.0 at.% Zn and 34.7-37.1 at.% Sb, is positively identified for the first time, and the crystal structure of VZnSb is not resolved. The VZnSb ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Konyk et al [45] claimed a NiAs-type solid solution V 1Àx Cu x Sb at about 50 at.% Sb (x max ¼ 0.18) in the isothermal section of the V-Cu-Sb system at 500 C. EPMA data were presented for x Cu ¼ 0.115, 0.134, 0.181, but data were neither given for smaller Cu-concentrations nor for the binary V-Sb phase. The most recent investigation of V-Zn-Sb isothermal section at 450 C [46] also reported the existence of VSb that solves up to 9 at.% Zn. Similar observations were reported by Lomnytska et al in the systems V-Ni-Sb [47] and V-Sb-Si [48] at 800 C. In the V-Ni-Sb system at 800 C, the VSb phase was reported to solve up to 16 at.% Ni (V 0.84 Ni 0.32 Sb 0.84 ) [47], while the solubility of Si in the same phase at the same temperature was not more than 5 at.% [48].…”
Section: The Phase "Vsb"mentioning
confidence: 95%
“…Konyk et al [45] claimed a NiAs-type solid solution V 1Àx Cu x Sb at about 50 at.% Sb (x max ¼ 0.18) in the isothermal section of the V-Cu-Sb system at 500 C. EPMA data were presented for x Cu ¼ 0.115, 0.134, 0.181, but data were neither given for smaller Cu-concentrations nor for the binary V-Sb phase. The most recent investigation of V-Zn-Sb isothermal section at 450 C [46] also reported the existence of VSb that solves up to 9 at.% Zn. Similar observations were reported by Lomnytska et al in the systems V-Ni-Sb [47] and V-Sb-Si [48] at 800 C. In the V-Ni-Sb system at 800 C, the VSb phase was reported to solve up to 16 at.% Ni (V 0.84 Ni 0.32 Sb 0.84 ) [47], while the solubility of Si in the same phase at the same temperature was not more than 5 at.% [48].…”
Section: The Phase "Vsb"mentioning
confidence: 95%
“…The static method, which had been adopted by our and other groups, [20][21][22][23][24] was used to measure the solubility of polystyrene in sub-R134a. A schematic diagram of the solubility measurement apparatus is shown in Fig.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…And the phenomenon of solute solubility was the same previously reported. 21,26 According to the theory of Flory and Huggins, 27,28 this phenomenon could be attributed to the stronger interactions between solute molecules than between solvent and solute with high molecular weight; meanwhile, the relative Gibbs free energy (ΔG) between polymer and solvent increased with increasing polymer chain 29 ; and according to Eqn (3), this results in a decrease of the combinatorial entropy effects (ΔS) and then leads to a reduction of the solubility of polymer:…”
Section: Solubility Of Polystyrene In Sub-r134amentioning
confidence: 99%
“…The calculated results are in good accord with the experimental data at 600°C. [20] To provide reliable information on the phase equilibria relevant to hot-dip galvanizing, phase relations in the Zn-VSb ternary system have been studied experimentally at 450°C, [22] and at 600 and 800°C. [23] Zhu et al [22,23] found a new ternary compound with a formula of VZnSb, whose composition range spanned from 30.4 to 32.4 at.% V, 30.5 to 34.0 at.% Zn and 34.7 to 37.1 at.% Sb at 450°C.…”
Section: Literature Datamentioning
confidence: 99%